The Arabian nights, tales of wonder and magnificence - Colum, Padraic 1881-1972.; Ward, Lynd 1905-. (New York Macmillan, 1953)
Selections from the over 600 stories which, according to legend, Shaharazad told a mighty king as a way to save the lives of the girls of her land. Includes stories of the voyages of Es-Sindibad, the magic horse, the wonderful lamp, and Ali Baba and the thieves.
Keywords: Folklore, Arab; Fairy tales